The hidden curriculum in the Mexican history books in the Mexican Baccalaureate (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
This research analyzes the didactic content of the textbooks of History of Mexico at the baccalaureate level. A qualitative methodology of descriptive type was used. The use of Discourse Analysis (AD) made it possible to identify the political, economic and educational context under which the contents of the textbooks are defined, as well as the participation of foreign publishers that are part of this process and whose intervention in the Content creation is also fundamental. It is concluded that the textbooks of the subject represent a nationalist rather than a didactic discourse. Based on the information analyzed, a curriculum is proposed that develops in the student the necessary skills to achieve historical empathy and meaningful knowledge.
Keywords: hidden curriculum; didactics; nationalism; teaching of history; history of Mexico